RELATIONSHIP BETWEEN COMPOSITION AND LATTICE PARAMETERS OF SOME SEDIMENTARY DOLOMITE VARIETIES - McCarty D.M.; Drits V.A.; Sakharov B. (My University, 2006)
A representative collection of iron-poor non-stoichiometric sedimentary dolomite samples of various composition, location, and age was studied by X-ray qualitative and quantitative phase analysis as well as by coupled plasma-atomic emission (ICP-AES) and X-ray fluorescence (XRF) spectroscopy. The main task is to determine relationships between the lattice parameters and Ca content in non-stoichiometric dolomite. It is found that the unit cell parameters as well as the lattice hkl spacings of the studied dolomite samples are related by the following linear equations with strong linear correlation coefficients:c = 7.3097a-19.135 R = 0.9988 a=1.0306d( 104) +1.8337 R = 0.9991 c = 7.6284d104)-6.0059 R=0.9984 ceff=7.4038aeff-19.59 R = 0.9991 aeff= 1.0251d(104)+1.8499 R = 0.9989 aeff = 1.8215d( 113) + 0.8157 R = 0.9990 ceff= 7.5244d(104) -5.7065 R = 0.9983 where aeff=d(110) +d(030) and ceff= 6d(006). These almost perfect interdependences exist because in the studied dolomite structures not only unit cell parameters (as expected by Vergard's Law), but also corresponding hkl spacings co-vary in a linear manner with Ca content as follows: c = 0.8632nca+15.14 R = 0.9971 a = 0.1168nca + 4.6903 R = 0.9967 a(104) = 0.119nca + 2.7658 R = 0.9981 a eff =0.11967nca+4.6872 R = 0.9975 ceff =6rf(006) = 0.8852/nca +15.1146 R = 0.9958. The validity of these equations is confirmed by a comparison of Ca contents determined by the regressions and chemical analysis for monophase dolomite samples for which 1.00 < nca < 1.07 where nca is the average amount of Ca per structural unit. The difference between the compared Ca contents determined for each monophase sample by the two independent techniques in average is equal to 0.005 atoms of Ca per structural unit. The standard deviation determined for the 47 studied samples is equal to 0.004 atoms of Ca or0.002 mol % CaCO 3. Excess-Ca dolomite samples for which nca < 1.09 consist of two dolomite phases with different amounts of excess Ca. Quantitative determination of proportions of each of these phases in the two-phase dolomite samples was carried out using the Rietveld software program Autoquan®. The lattice parameters and hkl spacings are used to determine Ca content in each of these phases using the regressions obtained for the monophase samples. Comparison of the calculated average Ca content with that determined from the chemical analysis shows that in average the difference between the compared values are equal to ± 0.012 atoms ofCaperformulaor ± 0.06mol %CaC03. The results are in accordance with a structural model where only the B sites have a mixed occupancy confirming the results of a previous work. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: DOLOMITE PHASE COMPOSITION; EXCESS-CA DOLOMITE; LATTICE PARAMETERS; UNIT CELL REFINEMENT; X-RAY DIFFRACTION